Collaboration requirements for project management information systems and its implications to project knowledge management - Verdezoto, Ivan (My University, 2013)
More and more organizations are changing their way of managing projects, switching from a traditional and controlled to a more flexible bottom-up paradigm, where collaboration and knowledge sharing between internal and external project members are critical factors. In addition, the role of technology is increasing in the context of project management due to greater challenges in today’s technology-enabled work environment, where technology tools are habitually used for collaboration, communication, and deployment of project management practices The purpose of this thesis is to identify and analyze current requirements of project management in project-based organizations regarding collaboration and knowledge management, as well as the impact of these requirements in use by practitioners on improving the management of projects. The research design and methodology were supported by main research questions. In order to collect the evidence to answer the questions a comparative case study approach was selected, which included several project-based organizations in Finland belonging mainly to the IT industry. In addition, the evolution and roadmap of a project management information system was presented and analyzed. The findings reveal the influence of collaboration and knowledge management to be incorporated in the management of projects through the use of socio-collaborative tools. An integrative project management framework combining these tools is presented.
Keywords: project management; collaboration; knowledge management; social technologies; collaboration technologies; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|